E-035 Intraoperative angiography during surgery for dural arteriovenous fistulas: a retrospective analysis. (16th November 2010) - Pandey, P; Dodd, R; Do, H; Steinberg, G; Marks, M
Abstract : Introduction: Intraoperative angiography is an important and valuable adjunct during surgery for a variety of neurovascular diseases. The utility of intraoperative angiography during arteriovenous malformation surgery has been described before. However, there are no reported series describing angiography use in surgery for dural arteriovenous fistulas (AVFs). Materials and methods: Over the past 15 years, intraoperative angiography was performed in 28 patients during surgery for dural AVFs after the surgeon felt the fistula was obliterated. The clinical details, surgical and angiographic (pre, intra and postoperative) findings, and postoperative outcomes of all other 28 patients were retrospectively reviewed. The incidence of residual fistula on intraoperative angiograms, and the utility to the surgical procedure was evaluated. The incidence of false negative intraoperative angiograms was also determined. Results: All patients (12 women, 16 men; aged 24–73 years) underwent direct surgery for dural AVF. These 28 patients had 30 dural arteriovenous fistulas (DAVFs) (two patients had multiple fistulas). The distribution of the fistulas were: transverse-sigmoid (n=9), tentorial (n=6), torcular (n=2), cavernous sinus (n=4), SSS (n=4), foramen magnum (n=3) and temporal/middle fossa (n=2). Presenting features were: hemorrhage related to fistula (n=14), hemorrhage not related to fistula (n=2), tinnitus (n=7), non-hemorrhagic neurological deficits (n=3), opthalmoplegia (n=3) and intracranial hypertension (n=1). 21 patients had cortical venous drainage (six patients had venous aneurysms). 11 patients underwent prior embolization while six patients had attempted but unsuccessful embolization procedures. Intraoperative angiography was done via the transfemoral route, with sheath insertion prior to positioning of the patient. Angiograms were technically possible in all patients, and all the vessels of interest could be catheterized. A total of 37 surgeries were done for the DAVF in 28 patients (30 DAVFs), and intraoperative angiogram was done in 33 of those surgeries. A total of 43 angiographic procedures were done in the 33 surgeries, with nine patients undergoing multiple angiograms until fistula obliteration. Postoperative angiography was performed in all patients to look for any residual fistula/early draining vein. In 11 patients (39.3%), intraoperative angiography revealed residual fistula and early draining vein after the surgeon determined that there was no residual fistula. This led to further exploration of the fistula in the same sitting in 10 patients, while in one patient, further surgical exploration was done at a later date. False negative intraoperative angiography occurred in three patients (10.7 %) where the intraoperative angiogram did not show any residual fistula but the postoperative angiogram showed a small residual. One patient was treated with repeat surgery, one with embolization followed by surgery and one with embolization alone. At the end of the treatment, none of them had any residual fistula. Of the 43 intraoperative angiograms, 40 correctly predicted either presence or absence of residual fistula. Only three angiograms (3/43, 6.9%) incorrectly predicted the absence of residual fistula. Conclusions: Intraoperative angiogram is an extremely important adjunct in the surgery for dural AVF. In this series, it resulted in further surgical treatment in 39.3% of patients. However, there is a 10% false negative rate which justifies subsequent postoperative angiography.